Fatigue Behavior of Direct Metal Laser Sintered (DMLS) Inconel 718 - Kelley, Paul. (2017)
Abstract: In the rapidly growing field of additive manufacturing (AM), the focus in recent years has shifted from prototyping to manufacturing fully functional, end-use parts, particularly using metals. In order for these parts to be designed to function both safely and effectively, it is necessary to have a thorough understanding of the mechanical behavior of materials produced via the AM process. This research focused on characterizing the high cycle fatigue (HCF) behavior of Inconel 718 produced via the Direct Metal Laser Sintering (DMLS) process. Material anisotropy in three orthogonal build orientations was evaluated along with the influence of the as-fabricated surface quality on fatigue performance. In addition to fatigue testing, surface roughness characterization, tensile testing, and fractography were performed on the additive manufactured specimens. Measured fatigue strength of specimens built in horizontal orientations was found to be greater than that of specimens built in the vertical orientation. Furthermore, fatigue lives of specimens with a machined surface were significantly greater (10 to nearly 1000 times) than those of specimens left as-fabricated by the DMLS process. Results showed that specimens produced in an optimal build orientation for the particular loading condition and with improved surface quality via machining correlated well with published fatigue data for traditionally processed and polished Inconel 718 specimens.; Thesis (M.S.)--Tufts University, 2016.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Anil Saigal.; Committee: Gary Leisk, and Anthony DiCarlo.; Keyword: Mechanical engineering.